Pendampingan Pengelolaan Website Desa Sebagai Bentuk Komunikasi Publik Pemerintah Desa - Jamiah, Ririn; Yuliasari, Alfiyana; Syahid, Ahmad (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2024)
The village website is a medium for the disclosure of various public information by the government. In line with this, Sumber Baru village, Seputih Banyak District, Central Lampung has a village website that the government can use as a communication medium for village programs, but its management is still not optimal. The aim of this service is to provide assistance to village operators to manage websites, especially in terms of writing articles, taking photos and managing website interface. The method used in this mentoring activity is the ABCD (Asset Based Community Development) method. This mentoring activity will be carried out in September-October 2023 and consists of 5 stages of mentoring, namely coordination, socialization, training, mentoring and evaluation. After completing the mentoring activities, the results of the mentoring can be seen directly on the village website and show that there has been an improvement in website management, such as an increase in the number of news/activities in Sumber Baru Village that are reported on the website. It is hoped that mentoring activities like this will be further increased to improve the quality of village human resources which will have an impact on improving public communication by the village government.            Keywords: mentoring; public communication; village website